Mechanisms of breast cancer risk in shift workers: association of telomere shortening with the duration and intensity of night work. (14th July 2017) - Samulin Erdem, Johanna; Notø, Heidi Ødegaard; Skare, Øivind; Lie, Jenny‐Anne S.; Petersen‐Øverleir, Marte; Reszka, Edyta; Pepłońska, Beata; Zienolddiny, Shanbeh
Abstract: Occupational factors such as shiftwork and especially night work that involves disruption of the circadian rhythm may contribute to increased breast cancer risk. Circadian disruption may also affect telomere length (TL). While short TL generally is associated with increased cancer risk, its association with breast cancer risk is inconclusive. We suggest that working schedules might be an important factor in assessment of effects of TL on breast cancer risk. Moreover, telomere shortening might be a potential mechanism for night work‐related breast cancer. In this study, effects of shift work on TL and its association with breast cancer risk were investigated in a nested breast cancer case–control study of Norwegian nurses. TL was assessed by qPCR in DNA from 563 breast cancer patients and 619 controls. Here, we demonstrate that TL is affected by intensive night work schedules, as work with six consecutive night for a period of more than 5 years was associated with decreased telomere lengths (−3.18, 95% CI: −6.46 to −0.58, P = 0.016). Furthermore, telomere shortening is associated with increased breast cancer risk in workers with long periods of consecutive night shifts. Thus, nurses with longer telomere lengths had a lower risk for breast cancer if they had worked more than four (OR: 0.37, 95% CI: 0.16–0.79, P = 0.014) or five (OR: 0.31, 95% CI: 0.10–0.83, P = 0.029) consecutive night shifts for a period of 5 years or more. These data suggest that telomere shortening is associated with the duration and intensity of night work and may be a contributing factor for breast cancer risk among female shift workers. Abstract : This study demonstrates that telomere shortening in night workers may be a plausible biological mechanism explaining the increased breast cancer risk in workers with long periods of consecutive night shifts. To our knowledge, this is a novel mechanism suggesting telomere shortening as a contributing factor for shift work‐related breast cancer risk.